(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to answer the perception of the hybrid-learning modality implemented by Bestlink College of the Philippines in terms of comprehension, Attendance, and examination. The results of this study reveal that in the process of hybrid learning, the male students of General Academic Strand Grade 12 can more easily understand and participate than female students. Even male students can easily participate and understand the lesson, but when it comes to attendance, they are equal. This study recommended that in blended learning, students get the opportunity to learn at any moment and in any place, and they may choose the time and place of their study. The respondents stayed fully engaged in class because of the blended learning session. Students have the option to learn in a variety of ways because of blended learning, and it is useful for developing the student’s participation in class.